An overview of targeted therapies in acute myeloid leukemia - Turkalj, Sven; Radtke, Felix A.; Vyas, Paresh (HemaSphere, 2023)
Acute myeloid leukemia (AML) is the most aggressive adult leukemia, characterized by clonal differentiation arrest of progenitor or precursor hematopoietic cells. Intense preclinical and clinical research has led to regulatory approval of several targeted therapeutics, administered either as single agents or as combination therapies. However, the majority of patients still face a poor prognosis and disease relapse frequently occurs due to selection of therapy-resistant clones. Hence, more effective novel therapies, most likely as innovative, rational combination therapies, are urgently needed. Chromosomal aberrations, gene mutations, and epigenetic alterations drive AML pathogenesis but concurrently provide vulnerabilities to specifically target leukemic cells. Other molecules, either aberrantly active and/or overexpressed in leukemic stem cells, may also be leveraged for therapeutic benefit. This concise review of targeted therapies for AML treatment, which are either approved or are being actively investigated in clinical trials or recent preclinical studies, provides a flavor of the direction of travel, but also highlights the current challenges in AML treatment.
Gesehen am 23.02.2026